PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA ONLINE SHOP THE ZENZY SHOES - Lusnia Nuriani, Lusnia; Syaifullah (SCIENTIA JOURNAL, 2022)
The purpose of this study was to determine whether product quality and service quality affect consumer satisfaction at The Zenzy Shoes Online Shop. The research was conducted using quantitative techniques. The population used consisted of 234 consumers of Online Shop The Zenzy Shoes. 234 consumers were used as research samples using probability sampling with simple random sampling technique. Questionnaires were used as a data collection technique. By using SPSS 25 software, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis testing. Based on the results of multiple linear regression, product quality (X1) has an effect of 0.352 or 35.2% on consumer satisfaction (Y) and service quality has an effect of 0.563 or 56.3% on consumer satisfaction (Y). Product quality and service quality factors affect consumer satisfaction by 80.0% according to the data of the coefficient of determination (R2). Based on the results of the t-test, product quality has a positive and partially significant effect on consumer satisfaction and service quality has a partially positive and significant effect on consumer satisfaction and the f test results show that product quality and service quality simultaneously have a positive and significant influence on consumer satisfaction.